Development of Interest in Particle Physics as an Eﬀect of School Events in an Authentic Setting - Gedigk, Kerstin; Kobel, Michael; Pospiech, Gesche (Scientia in educatione, 2017)
The Particle Physics Masterclasses are events oﬀered by the “Netzwerk Teilchenwelt”, a German network of particle physicists, students and teachers with the intention to make original data from CERN available for own measurements of students. These events were evaluated in 2011/2012. The investigation deals with their eﬀect on the interest development of the youth participants, especially in particle physics. With a focus on the role of diﬀerent event properties, it can be shown that besides the perceived challenge and comprehension, also authenticity is an important factor for the students’ interest development.